The Impact of Online Media Discourse on Public Opinion in Regional Elections: A Critical Discourse Analysis - Nila Kencana (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2024)
This study examines the influence of online media discourse on public opinion during the Bengkulu regional elections using a Critical Discourse Analysis (CDA) approach. The research focuses on the dominant narratives presented in online news and social media, highlighting themes such as economic development, political integrity, and candidates' personal character. Data were collected from multiple online platforms during the 2023 election campaign period, including major news websites and social media platforms like Facebook and Twitter. The findings reveal that economic development narratives had the strongest impact on voter sentiment, with candidates emphasizing local growth receiving more positive responses. While concerns about political integrity were present, they did not significantly influence voter behavior. Personal character emerged as a crucial factor, particularly on social media, where voters engaged more with narratives of trust and relatability. This study contributes to understanding the role of media framing in regional elections, reinforcing previous research on the impact of localized issues on voter behavior. The findings offer practical insights for political communication strategies in regional contexts and highlight the need for media literacy to critically engage with media discourse.